2012
DOI: 10.1103/physreve.85.021916
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of epidermal cells of whole living roots ofArabidopsis thaliana: An atomic force microscopy study

Abstract: The knowledge of mechanical properties of root cell walls is vital to understand how these properties interact with relevant genetic and physiological processes to bring about growth. Expansion of cell walls is an essential component of growth, and the regulation of cell wall expansion is one of the ways in which the mechanics of growth is controlled, managed and directed. In this study, the inherent surface mechanical properties of living Arabidopsis thaliana whole-root epidermal cells were studied at the nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 32 publications
5
38
0
Order By: Relevance
“…The first force measurements with AFM also invoked a nanoindenter, but with an improved lateral resolution down to a few nanometers (Kirby, 2011;Fernandes et al, 2012). More recently, quantitative force-volume mapping (QFM) was adapted to plant cell wall measurements utilizing continuous force curve recording and therefore solving the problem of heterogeneity observation by imaging the topography with the associated E and PI mappings.…”
Section: Structurementioning
confidence: 99%
“…The first force measurements with AFM also invoked a nanoindenter, but with an improved lateral resolution down to a few nanometers (Kirby, 2011;Fernandes et al, 2012). More recently, quantitative force-volume mapping (QFM) was adapted to plant cell wall measurements utilizing continuous force curve recording and therefore solving the problem of heterogeneity observation by imaging the topography with the associated E and PI mappings.…”
Section: Structurementioning
confidence: 99%
“…Several groups have recently achieved mechanical measurements made at a subcellular resolution in plants (Milani et al, 2011;Peaucelle et al, 2011;Fernandes et al, 2012;Radoti c et al, 2012;RoutierKierzkowska et al, 2012) using scaled-down indentation methods (Geitmann, 2006;Hayot et al, 2012;Milani et al, 2013;Routier-Kierzkowska and Smith, 2013), wherein one quantifies the force needed to push down on a sample to a prescribed depth. These studies have revealed spatiotemporal patterns of stiffness, notably in tissues (Milani et al, 2011;Peaucelle et al, 2011;Fernandes et al, 2012;RoutierKierzkowska et al, 2012).…”
mentioning
confidence: 99%
“…3), one obtains the local mechanical properties of the sample (e.g., Young modulus E, adhesion forces, stiffness, etc.). 20 Here we carried out force curve measurements and analyzed the results using a commercial analysis software, Bruker Nanoscope (Bruker AXS, Madison, WI). By fitting the approach curves (Fig.…”
Section: Afm and Force Curve Measurementsmentioning
confidence: 99%